2015
DOI: 10.3174/ajnr.a4218
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion and Perfusion MRI to Differentiate Treatment-Related Changes Including Pseudoprogression from Recurrent Tumors in High-Grade Gliomas with Histopathologic Evidence

Abstract: BACKGROUND AND PURPOSE Treatment-related changes and recurrent tumors often have overlapping features on conventional MR imaging. The purpose of this study was to assess the utility of DWI and DSC perfusion imaging alone and in combination to differentiate treatment-related effects and recurrent high-grade gliomas. MATERIALS AND METHODS We retrospectively identified 68 consecutive patients with high-grade gliomas treated by surgical resection followed by radiation therapy and temozolomide, who then developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
123
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(133 citation statements)
references
References 31 publications
3
123
0
7
Order By: Relevance
“…Some studies conclude that specific relative thresholds are helpful, with lesion-to-normal white matter rCBV ratio thresholds ranging from 1.2 to 2.0 for delineation of pseudoprogression (low rCBV) from recurrent disease (high rCBV) [35][36][37][38]. This is supported by studies in brain metastases demonstrating high reliability of detecting tumor progression (high rCBV) from radionecrosis (low rCBV) using a lesion to normal white matter rCBV ratio higher than 1.5-2.0 [39,40] and studies showing that rCBV can reliably differentiate radionecrosis from true progression in malignant gliomas [38,41].…”
Section: Perfusion Mrimentioning
confidence: 99%
“…Some studies conclude that specific relative thresholds are helpful, with lesion-to-normal white matter rCBV ratio thresholds ranging from 1.2 to 2.0 for delineation of pseudoprogression (low rCBV) from recurrent disease (high rCBV) [35][36][37][38]. This is supported by studies in brain metastases demonstrating high reliability of detecting tumor progression (high rCBV) from radionecrosis (low rCBV) using a lesion to normal white matter rCBV ratio higher than 1.5-2.0 [39,40] and studies showing that rCBV can reliably differentiate radionecrosis from true progression in malignant gliomas [38,41].…”
Section: Perfusion Mrimentioning
confidence: 99%
“…26,33,35 There were a total of 937 cases (54%) of tumor progression and 806 cases (46%) of treatment change. Investigators reported that pseudoprogression was the specific treatment effect under evaluation in 13 studies, 14,17,18,[29][30][31]33,34,[36][37][38][39][40] radiation necrosis in 4 studies, 15,16,19,21 and both in 2 studies. 25,34 Patients meeting inclusion criteria for pseudoprogression developed a new lesion during concurrent radiation and chemotherapy 29 out to 6 months after treatment completion.…”
Section: Selection Of Studies and Study Characteristicsmentioning
confidence: 99%
“…The remaining 28 studies met eligibility criteria for the systematic review. Seventeen studies evaluated DSC, [13][14][15]17,18,20,[23][24][25][27][28][29][30][31]34,36,39 8 evaluated DCE, 16,19,21,22,32,37,38,40 and 3 evaluated both DSC and DCE. 26,33,35 There were a total of 937 cases (54%) of tumor progression and 806 cases (46%) of treatment change.…”
Section: Selection Of Studies and Study Characteristicsmentioning
confidence: 99%
“…DSC-MR perfüz-yon incelmesinde, damar yoğunluğundaki artı-şın bir göstergesi olan CBV (cerebral blood volume-serebral kan akımı)'nin artması, tümöral neo-anjiogenezin dolaylı bir göstergesi olarak kabul edilmektedir [24,25]. Psödoprogresyon-da ise neo-anjiogenezin olmaması nedeniyle CBV değerleri düşüktür.…”
Section: Mr Perfüzyonunclassified